Interview with Teresa Corbin: Telstra’s Chief Customer Advocate - Corbin, Teresa; Morsillo, Robert (Journal of Telecommunications and the Digital Economy, 2023)
Teresa Corbin’s name was synonymous for many years with consumer advocacy in Australian telecommunication in her role as CEO of Consumers’ Telecommunications Network (CTN) from 2003 and Australian Communications Consumer Action Network (ACCAN) from 2010. In November 2021 Teresa joined Telstra Corporation Ltd as their Chief Customer Advocate. Here she speaks with Robert Morsillo about her new role, its opportunities and challenges, and how she sees Australian consumers engaging with telecommunications and the digital economy.